AFRICAN ADVENTURE ERNEST PSICHARI - (:unkn) unknown (My University, 2016)
Exploring Ernest Psichari’s texts from the Haut-Logone Mission directed by Commandant Lenfant, from literary history, this study attempts to answer the following questions: what does Africa means for Psichari ? How does it represent? What are the challenges of these figures and representations? What relationship with the post-colonial situation? This research shows that Africa is virtually the only part of its productions. More than a frame, more than a decoration, it is a living actant which through its ubiquitous action transforms other actants. But it remains a civilized land. This ambiguity is maintained by the fact that Psichari’s thought and ideals or his writing style leaves undecided. He seems both near and far natives. Impressionist and languid tone of his work, between dream and reality, alternates with passages more assertive and devoid of any sense of softness where the only patriotism is required. While displaying his love for the indigenous, defending their rights and cultures, Psichari does not hide his patriotism by working for colonization. This did not prevent him from rejecting the governmentality of the colonial system of the IIIe Republique.
Keywords: African Research